Does Size Matter for Female Continuous-flow LVAD Recipients? A Translational Approach to a Decade Long Question. Issue 1 (January 2022) - Anne Dual, Seraina; Nayak, Aditi; Hu, Yingtian; Schmid Daners, Marianne; Morris, Alanna A.; Cowger, Jennifer
Abstract : Females have increased risk of right-ventricular failure (RVF) and 3 month mortality after left-ventricular assist device (LVAD) implantation. In this translational study, we tested the hypothesis that sex differences in outcomes are driven by pump-induced LV size-volume mismatch, due to a negative impact on interventricular septal (IVS) interdependence. Adult continuous-flow LVAD recipients from the International Society For Heart And Lung Transplantation Mechanically Assisted Circulatory Support registry (n = 15, 498) were studied to determine association of female sex with outcomes of 3 month mortality and RVF. Female sex was associated with smaller preimplant left-ventricular end-diastolic diameter (6.5 vs. 6.9 cm, p  < 0.001), increased 3 month mortality (odds ratio [OR]: 1.42, p  < 0.001) and RVF (OR: 1.18, p  = 0.005). Smaller left-ventricular end-diastolic diameter was associated with worse outcomes after LVAD implantation (OR for mortality: 1.20, p  < 0.001; RVF: 1.09, p  < 0.001), and attenuated the association of female sex with these outcomes. In test bench heart phantoms (n = 4), the IVSs of smaller hearts demonstrated abnormal leftward shift earlier than larger hearts (volume change at IVS shift: 40 [95% confidence interval: 30–52] vs. 50 [95% confidence interval: 48–69] ml). Smaller LV size partially mediates worse post-LVAD outcomes for female patients, due to lower volume thresholds for adverse IVS shifting.